The Mental Structure of the Subordinate Concept “Work” (Part 2) - Науменко, Л. П. (Київський національний університет імені Тараса Шевченка, 2019)
The paper is devoted to cognitive analysis of the professional concept “work” as a subordinate concept of the macroconcept “business” connected with it by semantic notional relations. The inner form of the word-nominator work, its derivative, semantic, word-building, text-сomposing potentials, theoretical rethinking in scientific research, as well as semantic links with other possible names of the concept have been studied. It has been developed the architectonics of the concept, i.e. its notional, sense (sense centers / semantic kernels), imagery (image-stereotype “working woman” in its two formats – prototypical image and evaluative stereotype) and schematic (action frame which includes cause, contact action and characterization relations) components.

Стаття присвячена когнітивному аналізу концепту “work”, який посідає субординаційний рівень по відношенню до макроконцепту “business” і пов’язаний з ним семантико-поняттєвими зв’язками. Вивчається внутрішня форма слова-номінатора концепту, його дериваційний, семантичний, словотвірний та текстотвірний потенціал, теоретичне осмислення в наукових працях, семантичні зв’язки з іншими можливими номінаторами концепту. Розробляється ментальна структура концепту, а саме його поняттєвий, смисловий (смислові центри / семантичні ядра), образний (образстереотип “working woman” у двох форматах – прототиповий образ та оцінний стереотип) і схематичний (акціональний фрейм з відношеннями каузації, контактної дії й характеризації) компоненти.
Ментальна структура субординаційного концепту “Work” (частина 2)
Keywords: mental structure; subordinate concept; notional component; sense center; imagery component; action frame; ментальна структура; субординаційний концепт; поняттєвий компонент; смисловий центр; образний компонент; акціональний фрейм